2016
DOI: 10.9770/jesi.2016.3.3(3)
|View full text |Cite
|
Sign up to set email alerts
|

Design management as a domain of smart and sustainable enterprise: business modelling for innovation and smart growth in Industry 4.0

Abstract: The prior research has scrutinised the extent and scope of design integration for smart production and services innovation and value generation for smart society including enterprises, customers and end-users in the context of Industry 4.0. A conceptual approach has been proposed for practical business applications in developing and exploiting new innovative products or services. The present paper underpins the earlier research in methodological terms and is an affiliated research endeavour. The research trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 61 publications
2
31
0
1
Order By: Relevance
“…It turns out that strategic corporate governance is a very important determinant for organizational culture. For example, one study suggests how small enterprises within the Industry 4.0 domain can speed up their growth targets and grow to be more innovative, innovation being the move towards sustainable competitiveness and smart growth [23].…”
Section: Discussionmentioning
confidence: 99%
“…It turns out that strategic corporate governance is a very important determinant for organizational culture. For example, one study suggests how small enterprises within the Industry 4.0 domain can speed up their growth targets and grow to be more innovative, innovation being the move towards sustainable competitiveness and smart growth [23].…”
Section: Discussionmentioning
confidence: 99%
“…Other articles deal more strictly with the implications of IIoT for business models (Arnold et al 2016) and how the new business models of the digital era can be identified and developed (Pisano et al 2015;Najmaei 2016). Of particular interest is the emergence of these new business models in the context of the DT through entrepreneurship (Guo et al 2017), as well as their more sustainable nature (Gerlitz 2016;Prause and Atari 2017).…”
Section: Innovationmentioning
confidence: 99%
“…They answer questions like, who are customers, what to offer them, and how to operate to create value in profitable/sustainable way [1]. Authors of References [63][64][65][66][67] propose three interconnected value domains of a business model: Value proposition (reason why customers turn to one company over another), Value creation (resources, capabilities, and processes required to deliver the value proposition), and Value capturing (cost structure and revenue formula, which defines the profitability and economical sustainability of the business enterprise). As there is as an enormous value to management to have a software-based version of a business model, References [47,68,69] introduced its Business Model Canvas (BMC), composed of nine elements divided into four categories: Product (what?…”
Section: Business Modelsmentioning
confidence: 99%